A SEMANTIC ANALYSIS OF FIGURATIVE LANGUAGE IN SELENA GOMEZ’S ALBUM RARE - Rambi, Angela; Kumayas, Tirza; Olii, Sanerita T. (KOMPETENSI, 2022)
The purpose of this study is to analyze the types and the meaning of figurative language in the song lyrics of Selena Gomez in her album, Rare. The basis of this research is the theory proposed by Kennedy who divided figurative language in three parts, namely comparative, contradictive and correlative figurative language. In analyzing the data, the researcher used steps by Miles and Huberman: data reduction, data display and conclusion drawing and verification. The result of this research showed that there are 31 expressions of figurative language in six song lyrics of Selena’s “Rare” album. There are 22 expressions of metaphor, 6 expressions of hyperbole and 3 expressions of symbol. Metaphor is the most dominant figurative language in Selena’s song lyric; for example, in the lyric of Lose You to Love Me, we can found some expressions of metaphor, such as: set fire to my purpose and every single words builds up to this moment. From the explanation above, the researcher can suggest for future researcher to analyze and discuss other types of figurative language in Selena’s other album.